2016
DOI: 10.1175/jhm-d-15-0122.1
|View full text |Cite
|
Sign up to set email alerts
|

The Evaporative Demand Drought Index. Part II: CONUS-Wide Assessment against Common Drought Indicators

Abstract: Precipitation, soil moisture, and air temperature are the most commonly used climate variables to monitor drought; however, other climatic factors such as solar radiation, wind speed, and humidity can be important drivers in the depletion of soil moisture and evolution and persistence of drought. This work assesses the Evaporative Demand Drought Index (EDDI) at multiple time scales for several hydroclimates as the second part of a two-part study. EDDI and individual evaporative demand components were examined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
107
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(109 citation statements)
references
References 50 publications
2
107
0
Order By: Relevance
“…Considering the importance of proactive disaster managements (Wilhite et al, ), monitoring early‐stage droughts is crucial to prepare for disastrous droughts that can follow. It has been shown that some drought events in the CONUS were led by earlier above‐normal ET p (Hobbins et al, ; McEvoy et al, ), thus emphasizing the importance of tracking the heat wave‐driven droughts. On the contrary to SEDI, a precipitation‐based drought index such as SPI and SPEI is unlikely able to detect the flash drought.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Considering the importance of proactive disaster managements (Wilhite et al, ), monitoring early‐stage droughts is crucial to prepare for disastrous droughts that can follow. It has been shown that some drought events in the CONUS were led by earlier above‐normal ET p (Hobbins et al, ; McEvoy et al, ), thus emphasizing the importance of tracking the heat wave‐driven droughts. On the contrary to SEDI, a precipitation‐based drought index such as SPI and SPEI is unlikely able to detect the flash drought.…”
Section: Discussionmentioning
confidence: 99%
“…SEDI can thus supplement this weakness of precipitation‐based indices. As an alternative, it may be possible to monitor ET p for the heat wave droughts as in McEvoy et al (); nonetheless, in this case, the nonlinearity between ET p and ET a might hinder a proper indication of water deficit‐driven droughts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Otkin et al (2013) initially examined flash droughts via the satellite-derived Evaporative Stress Index (ESI) (Anderson et al 2007a(Anderson et al , 2007b. Subsequently, the Rapid Change Index (RCI) was derived from temporal changes in ESI and used to explore the relationship between rapid drought development and changes in evaporative stress (Otkin et al 2014(Otkin et al , 2015 Similarly, Hobbins et al (2016) and McEvoy et al (2016) leveraged atmospheric demand via the Evaporative Demand Drought Index (EDDI) to monitor the development of flash drought while Ford et al (2015) examined the utility of soil moisture for monitoring flash drought. Each of these methods provides one to two weeks of lead time with respect to drought impacts on the environment (i.e., significant reduction of soil moisture, stress on vegetation and agriculture, etc).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, it has been suggested that the AED may be the single most useful variable to quantify drought severity [3]. Accordingly, drought indices based only on AED have been recently formulated under the premise that AED anomalies are strongly connected with precipitation, soil moisture and actual evapotranspiration (ET) anomalies [4,5].…”
Section: Introductionmentioning
confidence: 99%